Increased risk of biliary infection after biliary stent placement in users of proton pump inhibitors. Issue 1 (22nd May 2022) - Hakuta, Ryunosuke; Nakai, Yousuke; Oyama, Hiroki; Noguchi, Kensaku; Kanai, Sachiko; Nomura, Yusuke; Suzuki, Tatsunori; Ishigaki, Kazunaga; Saito, Kei; Saito, Tomotaka; Hamada, Tsuyoshi; Takahara, Naminatsu; et al.
Abstract: Objectives: Proton pump inhibitors (PPIs) are widely prescribed medications for gastric acid‐induced diseases. Despite the effectiveness of PPIs, recent evidence suggested an increased risk of various bacterial infections in PPI users. The current study was conducted to evaluate the risk of biliary infection after endoscopic biliary stent placement in regular users of PPIs. Methods: Consecutive patients with a native papilla who underwent endoscopic retrograde cholangiopancreatography and stent placement for biliary stricture between January 2010 and August 2019 were included in this retrospective study. The cumulative incidences of biliary infection were compared between regular and non‐regular PPI users. Results: During the study period, 270 regular PPI users and 146 non‐regular PPI users were included in the analyses. Age, gender, and indication of endoscopic retrograde cholangiopancreatography were not different between the two groups. The incidences of biliary infection were 43% in regular PPI users and 36% in non‐regular PPI users but the time to biliary infection was significantly shorter in regular PPI users than in non‐regular users (28 vs. 87 days, p = 0.01). The cumulative incidence of biliary infection was significantly higher in regular PPI users compared with non‐regular users ( p = 0.008). The multivariable Cox regression analysis also showed a significantly higher hazard ratio of biliary infection in regular PPI users (1.62 [95% confidence interval 1.16–2.26; p = 0.005]). Conclusions: Regular PPI use was associated with a higher risk of biliary infection after endoscopic biliary drainage. Inappropriate PPI use should be avoided.